Exploring learning motivation and challenges among Indonesian students : Kulliyyah of Education International Islamic University Malaysia (IIUM) - Febrian, Ratih (Kulliyyah of Education, International Islamic University Malaysia, 2015)
Nowadays, people are interested in continuing with their studies although they already have a comfortable life, having established family and career. Some of them want to continue studying overseas. It is interesting to observe that there are Indonesian students at various stages of their life studying at IIUM. Their ages range from the 20s to the 50s. Some are already secured in their academic careers in Indonesia, married with children and some are supporting their families. This study is particularly concerned with students from Indonesia currently pursuing postgraduate studies at IIUM. Adopting the qualitative design, six Indonesian postgraduate students were interviewed to investigate and explore their motivation to continue with their education in a foreign country despite the risks and hardship they face. It appears that the respondents had internal motivation (self-development and obtainment of new challenges and experiences) as well as external motivation (job attainment, fulfilling the demand to be a role model in the family and establishing of school). Various factors seem to contribute to the decision to continue their education, particularly abroad such as the availability of financial resource, inspiration from those around them, support from others, family's educational background, conducive environment in destined country, influence of religious belief and the character of the institution itself. They experienced both internal and external challenges during the process of studying; internal challenges included language proficiency and time management problems, and external challenges were financial difficulty, academic and family matters. To overcome the challenges, the respondents applied various strategies such as improving language proficiency, managing time and task properly, seeking financial support, applying various learning strategies, seeking help from others, and practising religious teachings.